1994
DOI: 10.1007/bf01407745
|View full text |Cite
|
Sign up to set email alerts
|

Including spirituality in counsellor education: Issues for consideration, with illustrative reference to a New Zealand example

Abstract: The appropriate inclusion of spirituality in professional counsellor education programmes requires a careful definition of spirituality, and clarification of how it affects the programme's content. It also involves determination of how a programme may be structured to address various aspects of spirituality. This article highlights some of the issues involved in these tasks. SummarySpirituality in this article is defined as 'having to do with a person's innermost being and its connection with a universal force… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…They stated that it also means living out these values with discernible effects on oneself, others, and nature and on one's relationship with a higher power. Everts and Agee (1995) delineated several criteria that they considered important for practitioners and counselor educators to consider in the definition of spirituality. These criteria included accuracy, universality, affirmation, and a maximum potential for empirical validation.…”
Section: Definition Of Spiritualitymentioning
confidence: 99%
“…They stated that it also means living out these values with discernible effects on oneself, others, and nature and on one's relationship with a higher power. Everts and Agee (1995) delineated several criteria that they considered important for practitioners and counselor educators to consider in the definition of spirituality. These criteria included accuracy, universality, affirmation, and a maximum potential for empirical validation.…”
Section: Definition Of Spiritualitymentioning
confidence: 99%
“…The majority of clients who present themselves for counseling services have a religious foundation or spiritual beliefs (Cashwell & Young, ; Richards & Bergin, ), and these orientations should be included in the therapeutic assessment process (Everts & Agee, ; Johansen, ). Training counseling students to sensitively and respectfully discuss religious and spiritual beliefs with their clients can potentially provide counselors with a greater understanding of the meaning and importance attributed to clients' religious and spiritual views.…”
Section: Clinical Application Of Religious and Spiritual Beliefsmentioning
confidence: 99%
“…Therefore, assisting counseling students to understand, if not to use these methods, can influence psychological functioning in clients. Everts and Agee () suggested that for counselors to integrate these tasks effectively, counselor educators and supervisors must provide systematic attention, practice, and skills training toward student competencies and educational standards. They noted that students need to be trained to recognize their own beliefs and values related to spirituality and their role as a counselor.…”
Section: Addressing Spirituality and Religion In Counselor Training Pmentioning
confidence: 99%
See 1 more Smart Citation